2013
DOI: 10.1074/mcp.m112.024810
|View full text |Cite
|
Sign up to set email alerts
|

The Human Leukocyte Antigen–presented Ligandome of B Lymphocytes

Abstract: The presented HLA class I ligands are the products of the intracellular processing machinery, with its continuous cycle of protein synthesis and degradation (3). Much is known about the proteins involved in antigen processing, but high fidelity ligand/epitope predictions are at present not possible. The discovery of additional involved enzymes (3, 4) and the exciting discovery of peptide splicing (5) have shown that antigen processing is even more complex than was previously thought. Moreover, gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 58 publications
8
117
1
Order By: Relevance
“…Comparison of the complete dataset with recent large-scale studies revealed that 81% of the peptides have not been reported before (SI Appendix, Table S2) (16)(17)(18). Remarkably, the unique peptides identified in this study have distinct sequence characteristics compared with literature data (SI Appendix, Fig S4).…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Comparison of the complete dataset with recent large-scale studies revealed that 81% of the peptides have not been reported before (SI Appendix, Table S2) (16)(17)(18). Remarkably, the unique peptides identified in this study have distinct sequence characteristics compared with literature data (SI Appendix, Fig S4).…”
Section: Resultsmentioning
confidence: 53%
“…S9). Comparison with previous studies revealed that 16 HLA-B7-associated phosphopeptides had been reported previously (16,24,26), whereas a total of 24 phosphorylation sites are annotated in the Uniprot protein database (www.uniprot.org/). The correct identification of selected phosphopeptides could be nicely confirmed by the spectra we generated from their synthetic peptide counterparts (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In fact, MS/MS spectrum generation and acquisition is even more important in immunopeptidomics as compared to other sample types due to the very diverse physical chemical properties of these endogenous peptides 25. Thanks to tremendous technological development in the MS/MS field over the last decade, large‐scale MHC‐class I and MHC‐class II immunopeptidome analyses have taken off in recent years,6, 26, 27 thus drastically increasing the availability of immunopeptidome datasets.…”
Section: Lc‐ms/ms‐based Detection Of Immunopeptidomesmentioning
confidence: 99%
“…have reviewed the three main data acquisition concepts in MS that have been applied in immunopeptidomics,2 commonly used in other proteomics MS workflows. These include: 1) data‐dependent analysis (DDA) which is the widely used strategy for so‐called “discovery experiments” where the researcher is interested in profiling the repertoire of pMHC from a given sample5, 6; 2) selected reaction monitoring (SRM), also referred to as multiple reaction monitoring (MRM), targeted analyses whereby ion signatures from both the peptide precursor and its fragmentation product ions are monitored, and the area under the curve or peak height can be used for quantification purposes; this method ensures a higher degree of selectivity than a DDA experiment, but at the expense of the experimental depth and throughput7; and 3) data independent analysis (DIA) strategies, where all peptides within a defined mass‐to‐charge ( m/z ) window are subjected to fragmentation and recording of their combined MS/MS spectra; the precursor isolation window sequentially marches up the full m/z range and this analysis is repeated again and again during chromatographic elution 8. This less mature technique promises excellent performance for both discovery and quantitative analyses, especially with regard to reproducibility and more accurate label‐free quantification 9…”
Section: Introductionmentioning
confidence: 99%